PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP SISWA TENTANG ISOLASI MANDIRI COVID-19 DI SMPN 1 BANGSAL MOJOKERTO - Margaretha Luaq; Anndy Prastya; Dwi Helynarti Syurandhari (MEDICA MAJAPAHIT, 2023)
Covid-19 self-isolation is an effort made to prevent the transmission and spread of covid-19, by staying at home accompanied by monitoring health conditions and continuing to carry out health protocols, and keeping a distance from other family members. This study aims to determine the effect of health education on students' knowledge and attitudes about COVID-19 self-isolation at SMPN 1 Bangsal Mojokerto 2022. The research design used a pre-experimental design with a one-group pre-test post-test design approach. The sampling technique used is stratified random sampling with a total sample of 55 students of SMPN 1 Bangsal Mojokerto. The measuring instrument used is a pre-post test questionnaire. This research was conducted in May 2022. The results showed that almost half of the knowledge pre-test was in the sufficient category (45.5%) while the post-test results showed that most of them were in the sufficient category (74.5%). The pre-test on attitudes showed more than half in the moderate category (52.5%), then the post-test results showed almost all in the good category (78.2%). Based on the calculation of the Wilcoxon statistical test with p-value = 0.000 <a that is 0.05, H0 is rejected. Ha is accepted, so there is a significant influence on the Pre-Post test of students' knowledge and attitudes about COVID-19 self-isolation. The more information received, the more students' knowledge and attitudes about COVID-19 self-isolation will increase. Thus, it is recommended for schools to always cooperate with health workers to provide counseling about COVID-19 self-isolation.